Kegiatan Pengabdian Masyarakat Terhadap Deteksi Dini Gangguan Perilaku, Emosional, Dan Psikososial Di Sekolah Dasar Negeri Maleber - Agustina Agustina; Kimberley Kimberley; Venrico Phandry; Adryanus Rinaldi; Fhilia Anasty Gumay; Derren Fusta; Bramata Nagadiraja; Alexander Halim Santoso (Universitas Muhammadiyah Manado, 2024)
The aim of early detection of behavioral, emotional and psychosocial disorders in children is to identify students who require further examination based on the results of the examination. In this activity, interviews were conducted according to the Pediatric Symptom Checklist 17 (PSC-17) questionnaire. It is estimated that it can increase insight into the importance of early detection of behavioral, emotional and psychosocial problems so that it can improve children's well-being and academic success.